2017
DOI: 10.1056/nejmoa1706450
|View full text |Cite|
|
Sign up to set email alerts
|

Olaparib for Metastatic Breast Cancer in Patients with a Germline BRCA Mutation

Abstract: Among patients with HER2-negative metastatic breast cancer and a germline BRCA mutation, olaparib monotherapy provided a significant benefit over standard therapy; median progression-free survival was 2.8 months longer and the risk of disease progression or death was 42% lower with olaparib monotherapy than with standard therapy. (Funded by AstraZeneca; OlympiAD ClinicalTrials.gov number, NCT02000622 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
2,096
0
84

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 2,613 publications
(2,224 citation statements)
references
References 20 publications
44
2,096
0
84
Order By: Relevance
“…Both studies showed improvement of median PFS with the PARP inhibitor of ~ 3 months and greater tolerability, with no overall survival benefit evident as yet. Among patients with measurable disease, the objective response rates were approximately 60% with the PARP inhibitor compared to approximately 30% in physician choice (need to check talazaparib) [18,19]. The FDA approved olaparib for the treatment of germline BRCA1/2 metastatic breast cancer in January 2018.…”
Section: Germline Brca1 and Brca2 Mutation Status As A Hr Deficiencymentioning
confidence: 99%
“…Both studies showed improvement of median PFS with the PARP inhibitor of ~ 3 months and greater tolerability, with no overall survival benefit evident as yet. Among patients with measurable disease, the objective response rates were approximately 60% with the PARP inhibitor compared to approximately 30% in physician choice (need to check talazaparib) [18,19]. The FDA approved olaparib for the treatment of germline BRCA1/2 metastatic breast cancer in January 2018.…”
Section: Germline Brca1 and Brca2 Mutation Status As A Hr Deficiencymentioning
confidence: 99%
“…However, in further lines it can be reasonable to consider a treatment with a PARP inhibitor, although data are not consistent, whilst the EMBRACA trial with talazoparib demonstrated an equal and significant efficacy in both triple-negative metastatic breast cancer patients and hormone receptor (HR)-positive metastatic breast cancer patients (hazard ratio for PFS in HR-positive 0.47, 95% CI 0.32–0.71), the parallel OlympiAD trial showed a significant benefit of olaparib in triple-negative breast cancer only (hazard ratio for PFS in HR-positive 0.82, 95% C.I. 0.55–1.26) [4, 5]. Summarizing the results of both trials, the trend seems to be more in favor of using PARP inhibitors also in HR-positive metastatic breast cancer if a germline BRCA mutation has been found.…”
Section: Question 4: Should All Patients With Luminal Metastatic Breamentioning
confidence: 99%
“…Earlier this year, the FDA approved the BRACAnalysis CDx test for use in identifying patients with breast cancer with deleterious or suspected deleterious germline BRCA mutation (gBRCAm) who may be eligible for olaparib. The effectiveness of the BRACAnalysis CDx test was established based on the OlympiAD trial population [1]. There is emerging evidence that a significant number of patients with BRCA1/BRCA2 wild-type (wt) breast cancer is also deficient in homologous recombination, and it is likely that these patients may derive a similar benefit from drugs targeting DNA repair pathways, necessitating the development of a companion diagnostic to identify these sporadic BRCA-like tumors.…”
Section: Question 1: Do You Think That We Have the Optimal Drug Compamentioning
confidence: 99%